A comparative study of the effects of teacher-initiated planned preemptive and reactive focus on form on L2 learners' accuracy in narrative writing. Issue 1 (2nd January 2019) - Shabani, Karim; Hosseinzadeh, Somayeh
ABSTRACT: Although researchers in the area of second language acquisition agree on the effectiveness of form-focused instruction, there is little consensus on the appropriate time to direct learners' attention to linguistic items, that is, whether before or after the error occurrence [Nassaji, H. 2010, "The Occurrence and Effectiveness of Spontaneous Focus on Form in Adult ESL Classrooms." The Canadian Modern Language Review 66 (6): 907–933; Panahzade, V., and J. Gholami. 2014, "The Relative Impacts of Planned Preemptive vs. Delayed Reactive Focus on Form on Language Learners' Lexical Resource." The Journal of Language Teaching and Learning 4 (1): 69–83]. In this regard, adopting a quasi-experimental design, the present study attempted to compare the effects of two techniques of focus on form (FonF), namely teacher-initiated planned preemptive and reactive FonF, on the accurate use of English third person singular -s in L2 learners' narrative writing. Thirty-two English learners selected out of a total of 70 following a Quick Oxford Placement Test were randomly classified into two groups (one experimental and one comparison) each receiving a different FonF instruction during narrative tasks. Analysis of the groups' performance on the pretest, immediate posttest, and delayed posttest revealed that both techniques were equally beneficial in bringing the form in focus to the center of the learners' attention. It can, therefore, be suggested that the teachers need to observe the time when deciding to draw the learners' attention to the linguistic forms.